De novo genome assembly of rice bean (Vigna umbellata) – A nominated nutritionally rich future crop reveals novel insights into flowering potential, habit, and palatability centric – traits for efficient domestication - Kaul, Tanushri; Easwaran, Murugesh; Thangaraj, Arulprakash; Meyyazhagan, Arun; Nehra, Mamta; Raman, Nitya Meenakshi; Verma, Rachana; Sony, Sonia Khan; Abdel, Khaled Fathy; Bharti, Jyotsna; Gayacharan,; Badapanda, Chandan; et al. (Frontiers in Plant Science, 2022)
Rice bean is a less-known underutilized legume crop with a high nutritional value among members of the Vigna family. As an initiative to compose rice bean (Vigna umbellata) genomic resource, the size of 414 mega-base pairs with an estimated identification of 31,276 high confidence index genes via 15,521 scaffolds generated from Illumina and PacBio platform 30X coverage data has achieved 96.08% functional coverage data from Illumina and PacBio platform. Rice bean genome assembly was found to be exquisitely close to Vigna angularis (experimental control/outgroup), Vigna radiata, and Vigna unguiculata, however, Vigna angularis being the closest. The assembled genome was further aligned with 31 leguminous plants (13 complete genomes and 18 partial genomes), by collinearity block mapping. Further, we predicted similar discriminant results by complete coding sequence (CDS) alignment. In contrast, 17 medically influential genomes from the National Institute of General Medical Sciences-National Institutes of Health NIGMS-NIH, when compared to rice bean assembly for LCB clusters, led to the identification of more than 18,000 genes from the entire selected medicinal genomes. Empirical construction of all genome comparisons revealed symplesiomorphic character in turn uncovering the lineage of genetic and functional features of rice beans. Significantly, we found deserving late-flowering genes, palatably indexed uncommon genes that regulate various metabolite pathways, related to abiotic and biotic stress pathways and those that are specific to photoperiod and disease resistance and so on. Therefore, the findings from this report address the genomic value of rice bean to be escalated via breeding by allied and applied approaches.